The problem of partnership choices for scientific projects cooperation - Huilin Xu; Andrashko, Yurii (КНУБА, 2019)
The paper presents a formal statement of the problem of finding partners for the formation of a scientific consortium. The main features of partners (universities, research institutes, public authorities, private companies, professional associations and foundations), which influence the ways of communication and cooperation between them, are also defined. The list of factors influencing the creation of a partnership of scholars in the framework of a project or a grant is formed. The main methods of evaluating the activities of scientific institutions and universities in Ukraine and in the world are considered. It is determined that for the selection of scientific partners the criteria of known ratings do not allow to form a rational ranked list of potential partners of the project, therefore, they need to be finalized.
Keywords: scientific community; scientific project; choosing a partner; 338.33; 005.8:001